Building equitable access to knowledge through open access repositories - Koutras, Nikos, 1983- (Advances in library and information science (ALIS) book series., 2020)
"This book argues that open access repositories have the potential to provide an equilibrium among the interests of authors, publishers, and users of scientific publications and online published works"--